Defining the quality of business processes - Heinrich, Robert; Paech, Barbara (Modellierung 2010, 2010)
Business process models are used to gain a joint understanding of complex processes. Often they are applied in change projects where either the supporting IT or the processes themselves or both are to be improved. So it is an important question to assess the quality of the modeled business processes. However, so far there is no standard definition of the quality of a business process. Furthermore, business process models are not tuned to capture quality aspects. The goal of our work is to collect important quality characteristics and attributes of processes and to enhance business process modeling languages with means to express these attributes. This paper is a first step in this direction. We define a first set of quality characteristics, attributes and measures for these attributes in a business process. As an example we evaluate how well these measures can be expressed in a BPMN model.